Deep Potential: A General Representation of a Many-Body Potential Energy Surface (Communications in Computational Physics, 2018)
We present a simple, yet general, deep neural network representation of thepotential energy surface for atomic and molecular systems. It is "first-principle" based,in the sense that no ad hoc approximations or empirical fitting functions are required.When tested on a wide variety of examples, it reproduces the original model withinchemical accuracy. This brings us one step closer to carrying out molecular simulationswith quantum mechanics accuracy at empirical potential computational cost.
Keywords: Potential energy surface; deep learning; molecular simulation.